(untitled) (Vietnam Journal of Community Medicine, 2024)
Lung transplantation is an effective treatment for people with end-stage respiratory diseases. Lymphangioleiomyomatosis (LAM) is a rare cancer that involves the formation of air cysts that cause pneumothorax, impaired respiratory function, and also causes tumors in the abdomen and lymph nodes. LAM patients often have poor diagnosis, there is no specific treatment and only palliative treatment support, improving quality of life. We report a case of a female patient, 21 years old, with a historic diagnosis of LAM in 2021, removed a half of the left kidney in 2016 by surgery. Patients receive intensive care and treatment in a sterile area. After 7 weeks, the patient’s health condition improved, good nutritional status, normal movement, was discharged from the hospital for outpatient treatment, and was able to adapt with daily life.